Comparative study of different centrifugation protocols for a density gradient separation media in isolation of osteoprogenitors from bone marrow aspirate - Noel Ye Naung; Srisurang Suttapreyasri; Suttatip Kamolmatyakul; Thongchai Nuntanaranont (Elsevier, 2014)
Introduction: Human bone marrow contains osteoprogenitors capable of differentiating into osteoblasts. Density gradient centrifugation (DGC) is a commonly used method to isolate osteoprogenitors from bone marrow. Numerous studies used different dilution and centrifugation protocols, which might affect cell yields and quality. Moreover, the relative isolation efficiencies of the different separation protocols have not been investigated. This study compares the enrichment efficacy of the two different centrifugation protocols for a commonly used DGC media in isolation of osteoprogenitors. Material and method: Bone marrow was aspirated from human anterior iliac crests. Osteoprogenitors are isolated with Ficoll DGC media. A centrifugal force of 400 g and 1:1 dilution was compared with the centrifugal force of 1000 g after three dilution times with a buffer. Results: The average numbers of isolated cells were significantly higher when using lower centrifugal force with 1:1 dilution, however, there was no detectable difference between Colony-forming unit-fibroblast (CFU-F) forming capacity, STRO-1 positivity, osteogenic differentiation or mineralization abilities between protocols. Conclusion: Both protocols could isolate competent and functional osteoprogenitors, while a lower centrifugal force (400 g) with 1:1 dilution produced recovery of more osteoprogenitors.